Analisis Egalitarianisme Asma Barlas dalam Konsep â€œSakinahâ€ Alimatul Qibtiyah - Arfa'in, Muhammad Caesar (Jurnal Riset Agama, 2023)
The discourse on contemporary gender equality is an interesting study to discuss, especially more specifically in the family area. Alimatul Qibtiyah presents the direction of the Muslim feminism movement in Indonesia with a silent revolution approach, which is subtle, avoiding conflict and not frontal, of course starting from the family area. Alim's moderate-progressive style of feminist thought is to dissect the concept of sakinah so that it can be relevant in this contemporary era so that it has the value of equality, justice and equality. This research aims to describe the concept of sakinah according to Alimatul Qibtiyah who is influenced by Asma Barlas' egalitarianism. In this research, using qualitative methods and descriptive-analytical approach. The results of this study show that the three values of a sakinah family, namely kesalingan, justice and mashalah put forward by Alim become an upgraded area or development of Barlas' thinking even though in a specific area, namely contemporary family issues.